Net Working Capital Analysis: A Study on Consumer Durables Companies Traded on The Stock Exchange Istanbul (Third Sector Social Economic Review, 2025)
Working capital, which plays an important role in determining the financing needs of firms, refers to the investment made by firms in current assets, and current assets that cannot be managed effectively cause a net working capital deficit from time to time.In this study, the net working capital and current ratio adequacy of the firms operating in the consumer durables sector traded in Borsa Istanbul (BIST) were analyzed and at the same time, it was tried to determine the investment and financing policies they follow. For this purpose, the financial data of 9 firms operating in the relevant field for 5 periods between 2019 and 2023 were utilized.According to the results of the research, it has been observed that there are very few periods in which both net working capital and current ratio of the firms are sufficient in the same period, and in general, in the same period, when net working capital is sufficient, the current ratio is insufficient. Among the companies subject to the application, it is seen that the financial adequacy level of ALCAR, IHEVA, SAFKR, SNİCA followed a positive course only in 2022 and only SNİCA was successful in 2023. Moreover, while it can be clearly stated that VESTL followed an aggressive working capital financing policy and IHEVA followed a conservative working capital financing policy, it was not possible to make a definite judgment about the investment and financing policies followed by the other firms since their current ratios and net working capital fluctuated over the years.
Keywords: Working Capital Management; Networking Capital; Current Ratio; Inverstment Policies; Financing Policies